Constructing a Tool for Software Regression Testing Based on Crow Search Method - I. Khaleel, Shahbaa; Alghadanfary, Raghda Anan (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
The software testing phase is an essential phase of software development. Its aim is to ensure that the program meets the desired requirements of it. Through the testing process, errors are found in the programs so that they can be fixed before deployment, i.e. before being used or delivered to the customer. The program must also be tested after to be published and delivered, this is called regression testing and it is one of the basic activities in software development and it must be done in the software maintenance phase to ensure its reliability. In this research, a tool was built that selects the optimal test cases that are used in the regression testing phase, using artificial intelligence techniques. The Crow Search Algorithm was used in the test case selection, and after modifications and improvements were made to the algorithm, the Improved Crow algorithm was proposed, which generates and selects test cases that achieve the basic paths of the program based on the improved fitness function, the dynamic awareness probability value of the crow, and the spiral search mechanism for the crows. In addition, the genetic algorithm was used for these test cases prioritization.